Evaluación de tres protocolos para la extracción rápida de ARN total de tejidos de Prosopis juliflora (SW) - Michel-López, Claudia Yared; González-Mendoza, Daniel; Zapata-Pérez, Omar; Rubio-Piña, Jorge; Cervantes-Díaz, Lourdes; Bermúdez-Guzmán, Manuel de Jesús (Revista Mexicana de Ciencias Agrícolas, 2018)
The extraction of high quality genomic RNA for PCR amplification, from Prosopis spp., is complicated due to the presence of a high percentage of secondary metabolites that bind or co-precipitate nucleic acids. In the present study, we report a modified protocol of sodium dodecyl sulfate/phenol that includes the elimination of liquid nitrogen in the maceration process, β-mercaptoethanol in the extraction of buffer and step of precipitation of ethanol. The absorbance ratios A260/A280 of the isolated RNA were around 2 to 1.9, suggesting that the DNA fraction was pure and can be used for a subsequent PCR analysis. The RNA isolated by this protocol is of sufficient quality for molecular applications. This technique could be applied to other organisms that have similar substances that make it difficult to extract RNA. Finally, this proposal represents a fast, cheap and effective alternative for the isolation of genomic RNA from fresh leaves of Prosopis spp., even in low-tech laboratories.
Keywords: extraction; mezquites; PCR; RNA